Reducing output voltage undershoot of a buck in a DCM to CCM transition using non-linear control - Asuncion, Arlaindo V. (2009)
A Buck fed Full Bridge Converter is a Switch Mode Power Supply Topology. This topology has a PWM controlled Buck Converter front end feeding a Full Bridge Converter that is operating at a maximum fixed duty cycle. The controller regulates the output voltage of the topology by adjusting the Buck Converter duty cycle. Its advantages over other topologies are 1) High Efficiency, 2) High Packaging Density and 3) Low Complexity. One disadvantage of using this topology is that it contains an equivalent double L-C output filter. These are the buck L-C filter and the Full Bridge L-C filter. This configuration will typically have a lower bandwidth as compared to a buck that contains just a single L-C output filter. The lower bandwidth becomes a problem when the required dynamic load transitions between the continuous and the discontinuous mode operation of the Buck Stage. This work evaluates a proposed non-linear control method to improve the dynamic load response of a 12V/700W Buck fed Full Bridge Converter used for a Server PSU. A Freescale 56F8013 DSP was used to evaluate the proposed Non-Linear Control. The Proposed Non-linear Control is compared to an Analog Linear Control and Digital Linear Control by testing the SMPS output voltage transients during load current steps. Compared with the Analog Linear Controller, the proposed control was able to reduce the output voltage undershoot from 18% down to 10% of output voltage set point during a load current step up. Compared with the Digital Linear Controller, the proposed control was able to reduce the output voltage undershoot from 20% down to 10% of the output voltage set point during a load current step up.